Understanding the environment and social policy - Fitzpatrick, Tony (Understanding welfare : social issues, policy and practice, 2011)
"Tony Fitzpatrick has assembled a very thoughtful collection of chapters which examine the various ways in which social and environmental concerns intersect with one another. At a very general level, sustainability offers a neat and tidy way to reconcile them. But as this book usefully reveals, in practice they interact in ways that are far from straightforward." Professor Andrew Jordan, School of Environmental Sciences, University of East Anglia.